GREEN BUSINESS CANVAS: KIOSCHEBIBIT'S ENTREPRENEURIAL STRATEGY IN PLANT SEEDLING SUPPLY - Arianti, Yuni; Muttaqin, Ridlwan (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2025)
This paper focuses on formulating development strategies for Kioschebibit using the Business Model Canvas (BMC) approach alongside a SWOT analysis. The goal is to strengthen its competitive positioning and support long-term sustainability in the increasingly dynamic agribusiness sector. Kioschebibit is a micro-enterprise focused on providing plant seedlings, with strong growth potential driven by rising urban farming trends and increased environmental awareness. This research employs a qualitative descriptive method through a case study, utilizing data collection techniques such as observation, interviews, and documentation. The analysis reveals that Kioschebibit’s main strengths lie in its product variety, competitive pricing, and use of social media for marketing. However, challenges remain in distribution reach and digital marketing execution. External opportunities such as gardening trends and green initiatives present substantial growth potential, although threats like extreme weather and raw material fluctuations must be addressed. By integrating BMC and SWOT frameworks, this study proposes an adaptive and data-driven entrepreneurship strategy as a foundation for sustainable business development.